Sedimentological characteristics of debris flow Deposits within ice−cored moraine of Ebbabreen, central Spitsbergen - Pleskot Krzysztof (Polish Polar Research, 2015)
The Ebbabreen ice−cored moraine area is covered with a sediment layer of up to 2.5 m thick, which mostly consists of massive diamicton. Due to undercutting by lateral streams, debris flow processes have been induced in marginal parts of this moraine. It was recognized that the sedimentology of deposits within the deposition area of debris flows is the effect of: (1) the origin of the sediments, (2) the nature of the debris flow, and (3) post−debris flow reworking. Analysis of debris flow deposits in microscale (thin sections) suggests a common mixing during flow, even though a small amount of parent material kept its original structure. The mixing of sediments during flow leads to them having similar sedimentary characteristics across the deposition area regardless of local conditions (i.e. slope angle, water content, parent material lithology). After the deposition of sediments that were transported by the debris flow, they were then reworked by a further redeposition process, primarily related to meltwater stream action.